Synthesis and Antibacterial Activity of a Series of Heterocyclic Sulfonate Ligands and Their Metal Complexes - Xiao-Jun, Feng; Bi-Sheng, Dai; Cheng-Bai, Su; Zheng, Zheng; Lin, Wang; Hua-Ze, Dong (Asian Journal of Chemistry, 2012)
A series of heterocyclic sulfonate ligands and their barium(II), silver(I), manganese(II), zinc(II) and cobalt(II) coordination compounds have been synthesized. Through antibacterial activities experiments of these complex compounds, metal salts as well as ligands, the rational conclusion is arrived that antibacterial activities of these compounds come from metal ions.